Carboxylesterase Inhibitors: An Update - Zou, Li-Wei; Jin, Qiang; Wang, Dan-Dan; Qian, Qing-Kai; Hao, Da-Cheng; Ge, Guang-Bo; Yang, Ling (Current Medicinal Chemistry, 2018)
Mammalian carboxylesterases are key serine hydrolases that catalyze the hydrolysis of a wide variety of ester compounds in the corresponding carboxylic acids and alcohols. In human, two major carboxylesterases, CES1 and CES2, have been identified and well-studied over the past decade. CES1 inhibitors have potential applications in the treatment of hypertriglyceridaemia, obesity and type 2 diabetes, owing to that this enzyme plays prominent role in the metabolism of cholesteryl esters. CES2 plays crucial roles in the metabolic activation of many prodrugs including anticancer agents capecitabine and CPT-11. Co-administration with CES2 inhibitors may ameliorate CPT-11 associated lifethreatening diarrhea or improve the half-lives of CES2-substrate drugs. The important roles of carboxylesterases in both endogenous and xenobiotic metabolism arouse great interest in the discovery and development of potent and selective inhibitors against these enzymes. This review is focused on the application potentials and recent advances in the discovery and development of carboxylesterases inhibitors. The inhibitory capacities and inhibition mechanism of a variety of carboxylesterases inhibitors including synthetic, semi-synthetic and natural compounds are comprehensively summarized. Furthermore, the key structural features and structure-activity relationships (SARs) of different classes of CES1 and CES2 inhibitors are discussed. All information and knowledge summarized in this review will be very helpful for the medicinal chemists to design and develop more potent and highly selective carboxylesterases inhibitors for potential biomedical applications.
Keywords: CES1